Risk analysis in project appraisal - Pouliquen, Louis Y.; The World Bank. (Baltimore ; London : Published for the World Bank [by] the Johns Hopkins University Press, 1970)
The use of risk analysis in project appraisal work is described, and associated methodological problems are highlighted as part of a continuing effort to tackle the problem of uncertainty. A year's experience with the Port of Mogadiscio project supports the utility of risk analysis as a powerful technique that permits the use of a great deal of information that would otherwise be lost. It can accommodate uncertainty about both the viability of a marginal project and the suitability of the design or phasing of a project. The entire framework of risk analysis provides a highly efficient medium of communication, but it requires far more judgment than does traditional analysis. A major methodological problem involves the treatment of correlations between variables. If these correlations are not properly handled, results can be misleading. These conclusions lead to the recommendation that the World Bank should cautiously introduce risk analysis techniques for appraisal work. Consultants should be asked to use risk analysis whenever possible in projects involving problems of optimization or of choice among alternatives.
Includes bibliographical references.
lje 08/10/2018
Loans
Keywords: Finance; Risk; Economic development projects